Therapeutic gardens: historical context, foundations, and landscaping - Thais Akemi Sillmann; Paula Oliveira Marques; Claudia Fabrino Machado Mattiuz (Ornamental Horticulture, 2024)
The Therapeutic Garden can be conceptualized as a designated space engineered to engender benefits on physical, psychological, cognitive, and social well-being of its users, facilitated through either passive or active engagement with nature. This review explores the therapeutic function of gardens, encompassing their historical evolution, theoretical underpinnings, concepts, benefits, uses and design guidelines. The therapeutic attributes of plants have been acknowledged since antiquity, underpinning the belief that nature constitutes a primary agent in fostering well-being. This conviction gained traction during the Middle Ages, by the cloister gardens, which sought healing through a communion with nature. Nonetheless, this relationship waned during the Renaissance, only to resurface in the 18th century within the realm of hospital architecture, underscoring the necessity of reinstating therapeutic gardens as an indispensable adjunct for healing patients. In recent times, there has been a resurgence in the quest to reconnect with nature, driven by scientific research highlighting the myriad health benefits of nature exposure, that fundamental various theories such as the Supportive Gardens Theory, Restorative Gardens, and Healing Gardens. These pioneering studies have paved the way for further research exploring the psychological, physical, and social advantages of gardens. Designs for therapeutic gardens should prioritize user needs, drawing from a multidisciplinary approach rooted in evidence-based design principles. However, specific definitions regarding their form and function remain elusive, allowing for a diversity of activities and adaptability to cater to different users.